Assessment of Nutrition and Importance of School Conditions to the Health of Students Studying in Urban and Rural Conditions (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
One of the main factors determining children’s health is nutrition. During their education in secondary schools, students perform not only mental but also physical activities. During this period, students feel the need for foods with high energy value due to high energy spending. Improper organization of children’s nutrition in secondary schools reduces their educability and increases the body's susceptibility to various diseases.